Analisis Korelasi Rating Kepuasan Layanan Maxim pada Mahasiswa - Pebriana, Risky; Anisa, Nor (Universitas Methodist Indonesia, 2025)
This study aims to analyze the correlation between student satisfaction ratings and Maxim online transportation services in Gorontalo City. Using quantitative methods, data were collected through a questionnaire distributed to 50 student respondents who used Maxim. The analysis was carried out using statistical techniques to identify the relationship between various factors that affect student satisfaction, such as ease of access, speed of service, affordable prices, and driver friendliness. The results of this study show that there is a significant positive correlation between service satisfaction ratings, ease of access, price, and customer friendliness. Users who are satisfied with the ease of access and speed of Maxim's services tend to give higher ratings. Besides, the friendliness of the drivers and the condition of the vehicles also contribute to the overall satisfaction level. The study concludes that companies need to focus on improving the quality of services and additional features to maintain user loyalty and improve student satisfaction ratings.